2016
DOI: 10.1248/bpb.b15-00999
|View full text |Cite
|
Sign up to set email alerts
|

Indirubin 3′-Epoxide Induces Caspase-Independent Cell Death in Human Neuroblastoma

Abstract: Indirubin inhibits cyclin-dependent kinases by binding to their ATP-binding site, thereby exerting potent cytotoxicity on some tumor cells. We examined the anti-tumor effect of indirubin 3'-epoxide on human neuroblastoma cell lines (IMR-32, SK-N-SH, and NB-39). The results revealed potent cytotoxicity of indirubin 3'-epoxide against the IMR-32 (IC50: 0.16 µM) and SK-N-SH (IC50: 0.07 µM) cells. Furthermore, it also induced an increase of the sub-G1 population in the IMR-32 cells. Examination by Hoechst 33342 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In addition, it was shown that indirubin-3 0 -monoxime is an inhibitor of death-associated protein kinases (DAPKs) (Jung et al 2016). Recently, a study using Hoechst 33342 and annexin-V-propidium iodide staining revealed that the indirubin derivative indirubin-3 0 -epoxide induces caspase-independent apoptosis in human neuroblastoma cells, probably due to a DNA fragmentation and impairment of DNA repair (Kurita et al 2016). In addition to these mechanisms, indirubins can induce antiproliferative activities by binding the aryl hydrocarbon receptors (AhR), a ligand-activated transcription factor mainly involved in the regulation of xenobioticmetabolizing enzymes (Adachi et al 2001;Knockaert et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was shown that indirubin-3 0 -monoxime is an inhibitor of death-associated protein kinases (DAPKs) (Jung et al 2016). Recently, a study using Hoechst 33342 and annexin-V-propidium iodide staining revealed that the indirubin derivative indirubin-3 0 -epoxide induces caspase-independent apoptosis in human neuroblastoma cells, probably due to a DNA fragmentation and impairment of DNA repair (Kurita et al 2016). In addition to these mechanisms, indirubins can induce antiproliferative activities by binding the aryl hydrocarbon receptors (AhR), a ligand-activated transcription factor mainly involved in the regulation of xenobioticmetabolizing enzymes (Adachi et al 2001;Knockaert et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the sulfur-halogen interaction forces the oxirane moiety close to Cys-199, thereby accelerating the covalent bond formation between the oxirane and the thiol [76,86,87]. In addition, Kurita et al [98] demonstrated that these indirubin-3 -(O-oxiran-2-ylmethyl)-oxime derivatives possess potent cytotoxicity against human neuroblastoma IMR-32 and SK-N-SH cell lines, with IC 50 values of 0.16 and 0.07 µM, respectively. These molecules induce caspase-independent apoptosis by inhibiting DNA repair and causing DNA fragmentation in IMR-32 cells [76,98].…”
Section: Classes Of Anticancer Oximesmentioning
confidence: 99%
“…Indirubin, a CDK inhibitor, induces caspase-independent cell death in human neuroblastoma [46], while other indirubin derivatives induce cell death through the intrinsic caspase-9 pathway and/or activation of caspase-8 in breast cancer cells [47]. (±)-trans-7 and 9) and macrocycle meso-10 provoke a G 0 /G 1 cell-cycle arrest in the A375 cell lines after 48 h of treatment.…”
Section: Biologymentioning
confidence: 99%